Inquiry-Based Chemistry Education in a High-Context Culture: a Qatari Case Study - Qureshi, S.; Vishnumolakala, Venkat Rao; Southam, Daniel; Treagust, David (Springer Netherlands, 2016)
This research took place within the context of ongoing educational reforms to promote inquiry-based science instruction and a desire to draw evidence to inform adoptions of western pedagogical practices in a high-context culture like Qatar. We report on the outcomes from Process Oriented Guided Inquiry Learning (POGIL) in a foundation chemistry course based on students’ achievement, their perceived learning gains, and their self-efficacy. The study utilized quantitative data obtained from normalized content tests and instruments to measure perceived learning gains and attitudes and experience. Qualitative data from open-ended student questionnaires were analyzed to cross-validate findings from the study. Positive effects of POGIL during fall (semester 1) and spring (semester 2) semesters were evidenced by (a) improved mean scores and medium to large effect sizes for content test results, perceived learning gains, and self-efficacy levels and (b) a positive correlation between the measures of perceived learning gains and self-efficacy. Students self-reported increased self-efficacy, interest, and better understanding of concepts using the POGIL method. Comparing fall and spring semesters, student reluctance and negative perceptions of the POGIL approach gradually diminished. Students were able to adapt easily to POGIL—a method of teaching that they had not experienced before but which was compatible with the high-context culture in which they live. In addition, this study reflects the current condition of science learning in Qatar, where the emerging outcomes of educational reforms play an important role in preparing local students to transition into higher education.